Prolonged-release fampridine in multiple sclerosis: Improved ambulation effected by changes in walking pattern. (October 2016) - Zörner, Björn; Filli, Linard; Reuter, Katja; Kapitza, Sandra; Lörincz, Lilla; Sutter, Tabea; Weller, David; Farkas, Melinda; Easthope, Christopher S; Czaplinski, Adam; Weller, Michael; Linnebank, Michael
Background: Prolonged-release fampridine (PR-fampridine, 4-aminopyridine) increases walking speed in the timed 25-foot walk test (T25FW) in some patients (timed-walk responders) with multiple sclerosis (MS). Objective: To explore the effects of PR-fampridine on different aspects of walking function and to identify associated gait modifications in subjects with MS. Methods: In this prospective, randomized, placebo-controlled, double-blind, phase II study (FAMPKIN;clinicaltrials.gov, NCT01576354), subjects received a 6-week course of oral placebo or PR-fampridine treatment (10 mg, twice daily) before crossing over. Using 3D-motion-analysis, kinematic and kinetic parameters were assessed during treadmill walking (primary endpoint). Clinical outcome measures included T25FW, 6-minute walk test (6MWT), and balance scales. Physical activity in everyday life was measured with an accelerometer device. Results: Data from 55 patients were suitable for analysis. Seventeen subjects were timed-walk responders under PR-fampridine. For the total study population and for responders, a significant increase in walking speed (T25FW) and distance (6MWT) was observed. Gait pattern changes were found at the single-subject level and correlated with improvements in the T25FW and 6MWT. Physical activity was increased in responders. Conclusion: PR-fampridine improves walking speed, endurance, and everyday physical activity in a subset of subjects with MS and leads to individual modifications of the gait pattern.